2022-RA-725-ESGO Treatment patterns & outcomes of patients with locally advanced vulvar or vaginal cancer in British Columbia. (20th October 2022) - Leung, Emily; Tremblay, Cassia; Liao, Donna; Huang, Longlong; Sun, Shaun Zheng; Ko, Jenny
Abstract : Introduction/Background: As vulvar and vaginal cancers are rare malignancies, treatment is extrapolated from the cervical cancer field, in which concurrent chemoradiation is used. Thus, further studies are necessary to evaluate whether surgery, radiotherapy (RT), or combined chemoradiotherapy (CCRT) will benefit patients the most. Methodology: A retrospective chart review was conducted on patients diagnosed with vulvar or vaginal cancer in 2000–2017. Descriptive statistics were used to compare survival outcomes between surgery, RT only, and CCRT. Results: We included 688 patients with either vulvar (N=560, 81%) or vaginal cancer (N=128, 19%). Median age of diagnosis was 68 (range 27–98) years. In multivariate survival analysis, vulvar cancer was associated with more likelihood of death compared to vaginal cancer (Hazard ratio (HR): 1.50, p=0.042). For patients who received curative RT, median OS (mOS) was 63.8 months with concurrent chemotherapy vs 46.3 months without (p=0.75) for vulvar cancer; for vaginal cancer, mOS was 100.4 months with concurrent chemotherapy vs 66.6 months without (p=0.31). For those who received RT (N=224, 40%; HR: 0.80, p=0.25), adding chemotherapy was not associated with statistically significant improvement in OS for vulvar (N=101, 18%; HR: 0.80, p=0.30) or vaginal (N=51, 40%; HR: 1.31, p=0.41) cancers. Vulvar cancer patients who received ≥5 weeks of chemotherapy had better OS (HR: 0.78, p=0.038) vs <5 weeks of treatment. This effect on OS was not seen in vaginal cancer patients (HR: 0.95, p=0.86). In the 221 (32%) patients who had disease relapse, the most common patterns of relapse were the pelvis without RT (N=96, 43%) and the primary site where radiation was given (N=89, 40%). Conclusion: In this retrospective study, CCRT was not associated with significant improvements in survival for patients with vulvar or vaginal cancer compared to RT only. Future studies investigating novel therapies to treat these cancers are needed to improve patient outcomes.